Phonological skills are (probably) one cause of success in learning to read: A comment on Castles and Coltheart - Hulme, C; Snowling, M; Caravolas, M; Carroll, J (2005)
Castles and Coltheart (2004) argued that the causal link between children's underlying phonological awareness and success in learning to read remains unproven. We argue that the balance of evidence does favor such a causal link. We also argue, however, that learning to read depends on broader language skills and that, like other aspects of development, it needs to be seen in the context of a multicausal system. Copyright © 2005, Lawrence Erlbaum Associates, Inc.